Revision notes for the MRCS Viva - Sundaramurthy, Kanchana (London : JP Medical, 2010)
Exam preparation tool for intercollegiate MRCS oral examinations.Organised into two sections, the first devoted to chapters on basic sciences, the second to system specific surgery. For each topic, succinct notes provide candidates with a framework for answering the stem and secondary questions encountered in the exam.
1. General principles -- 2. System-specific surgery
Includes index
Keywords: General Surgery; Study Guide